2014
DOI: 10.1371/journal.pone.0102061
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Clinical Trial of Encapsulated, Cytochrome P450 Expressing Cells as Local Activators of Cyclophosphamide to Treat Spontaneous Canine Tumours

Abstract: Based upon promising preclinical studies, a clinical trial was performed in which encapsulated cells overexpressing cytochrome P450 enzyme isoform 2B1 were implanted around malignant mammary tumours arising spontaneously in dogs. The dogs were then given cyclophosphamide, one of the standard chemotherapeutic agents used for the treatment of mammary tumours. The dogs were assessed for a number of clinical parameters as well as for reduction in tumour size. The treatment was well tolerated with no evidence of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…We have performed a clinical trial in dogs using encapsulated cells to locally activate this chemotherapeutic after peritumoral injection [ 8 , 51 , 52 ]. Tumor reductions were also observed in this clinical trial in companion animals [ 52 ], supporting the notion that the mechanism of action is not due to a simple obstruction of the blood vessels leading to the tumor, since in this study, the capsules were administered by injection directly into the tissues round the tumor site. Further, CT-scans taken during and after angiography in our human pancreatic cancer trials showed the patency of the vessels after instillation of the capsules.…”
Section: Discussionmentioning
confidence: 99%
“…We have performed a clinical trial in dogs using encapsulated cells to locally activate this chemotherapeutic after peritumoral injection [ 8 , 51 , 52 ]. Tumor reductions were also observed in this clinical trial in companion animals [ 52 ], supporting the notion that the mechanism of action is not due to a simple obstruction of the blood vessels leading to the tumor, since in this study, the capsules were administered by injection directly into the tissues round the tumor site. Further, CT-scans taken during and after angiography in our human pancreatic cancer trials showed the patency of the vessels after instillation of the capsules.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, their handling in the lab does not represent any complications and can be treated as cells and be frozen without damage. Importantly, the use of cellulose sulphate encapsulated human cells is safe in patients as has been demonstrated in two human clinical trials (Löhr et al, 2014) and in a veterinary application (Michałowska et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Cell encapsulation is a classic technique that has been applied for the delivery of active therapeutic agents from entrapped cells (Acarregui et al, 2013;Gonzalez-Pujana et al, 2017). Their application ranges from insulin release therapy for type 1 diabetes (Orlando et al, 2014) to other life-threatening pathologies, such as cancer (Löhr et al, 2014;Michałowska et al, 2014); also, capsules in general represent the possibility of their localization in a desired area (Dangerfield et al, 2013). The capsule structure must be permeable in order to enable nutrients and waste flux but also the release of the therapeutic agent(s).…”
Section: Introductionmentioning
confidence: 99%
“…CMT, the same as human breast cancer (BC), can be characterized by expression of estrogen, progesterone and HER2 receptors. The involvement of companion dogs with spontaneous CMT in translational oncology is already seen in numerous publications and several ongoing clinical trials (13). Canine tumoroids developed from dog patients with spontaneous CMT could therefore provide a more representative and ethical translational model to test drug efficacy and toxicity in pre-human studies, as well as canine tumoroids could be an innovative screening tool in drug discovery, while reducing the number of experimental animals needed for in vivo studies.…”
Section: Introductionmentioning
confidence: 99%